Completing the Picture of the Roper Resonance - Segovia, Jorge; El-Bennich, Bruno [UNESP]; Rojas, Eduardo; Cloet, Ian C.; Roberts, Craig D.; Xu, Shu-Sheng; Zong, Hong-Shi (Amer Physical Soc, 2015)
We employ a continuum approach to the three valence-quark bound-state problem in relativistic quantum field theory to predict a range of properties of the proton's radial excitation and thereby unify them with those of numerous other hadrons. Our analysis indicates that the nucleon's first radial excitation is the Roper resonance. It consists of a core of three dressed quarks, which expresses its valence-quark content and whose charge radius is 80% larger than the proton analogue. That core is complemented by a meson cloud, which reduces the observed Roper mass by roughly 20%. The meson cloud materially affects long-wavelength characteristics of the Roper electroproduction amplitudes but the quark core is revealed to probes with Q(2) greater than or similar to 3m(N)(2).